2022
DOI: 10.1001/jamaneurol.2022.0323
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Natural History of Pediatric Large Vessel Occlusion Stroke

Abstract: IMPORTANCEThe incidence and natural history of large vessel occlusion (LVO) stroke in children is largely unknown. These knowledge gaps limit the uptake of reperfusion therapies and reduce the efficiency of pediatric acute stroke pathways.OBJECTIVE To determine the incidence and natural history of pediatric LVO stroke. DESIGN, SETTING, AND PARTICIPANTSThis retrospective population-based cohort study was conducted between January 2010 and December 2019, with a mean (SD) follow-up of 37.0 (28.8) months. Admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…10 Increasing appreciation of the poor natural history of LVO strokes in children may also be contributing to increased uptake of MT despite lack of clinical trial evidence. 11 A recent study done using the National Inpatient Sample reported increased utilization of MT in children in the United States over the period 2010-2019. 12 We extend the results of this study by highlighting that the majority of this increased utilization is in older children.…”
Section: Discussionmentioning
confidence: 99%
“…10 Increasing appreciation of the poor natural history of LVO strokes in children may also be contributing to increased uptake of MT despite lack of clinical trial evidence. 11 A recent study done using the National Inpatient Sample reported increased utilization of MT in children in the United States over the period 2010-2019. 12 We extend the results of this study by highlighting that the majority of this increased utilization is in older children.…”
Section: Discussionmentioning
confidence: 99%
“…Given strong evidence that endovascular therapies such as thrombectomy significantly benefit select adults with large vessel occlusion [ 26 ], there is increasing interest in the use of these therapies for children with stroke. Although there are no randomized controlled data, mechanical thrombectomy may be safe in children [ 27 ], and guidelines suggest that thrombectomy may be appropriate in some children with large vessel occlusion who otherwise have a poor prognosis [ 28 , 29 ]. However, children with stroke are at higher risk of vasculopathies, which may not be appropriate for thrombectomy or increase the risks of thrombectomy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a retrospective, population-based cohort study of childhood ischemic stroke in Australia demonstrated that children with large vessel occlusions who were treated with MT ( n = 13, with or without IV-tPA) had better functional outcomes compared with children with large vessel occlusions who were managed conservatively ( n = 26) [ 179 ]. The authors point out, importantly, that the absence of randomization or standardized MT selection criteria likely led to selection bias, and children who were treated with MT were older than those children managed conservatively, which may have driven, at least in part, the differences in outcomes.…”
Section: Therapeuticsmentioning
confidence: 99%
“…An analysis from a US hospital showed that the major source of pediatric stroke diagnostic delays was late presentation to the emergency department, suggesting that future interventions aimed improving community recognition of stroke symptoms could help alleviate these delays [ 203 ]. Though ongoing improvements in time to pediatric stroke diagnosis are needed, a recent Australian study of pediatric large vessel occlusions showed that the majority presented early enough to be eligible for MT (69% presented within 6 hours of symptom onset and 90% within 24 hours) [ 179 ].…”
Section: Therapeuticsmentioning
confidence: 99%